Complexities of nursing in healthcare waste management in hospitals - Ferreira, Maria José Carvalho; Ventura, Carla Aparecida Arena; Valadares, Glaucia Valente; Silva, Thiago Privado da; Silva, Laura Johanson da; Silva, Ítalo Rodolfo (Revista Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to understand how healthcare waste management is developed by nursing professionals in hospitals. Methods: qualitative research, whose theoretical and methodological frameworks were Complexity Theory and Grounded Theory. Thirty-two nursing professionals from a public hospital in Rio de Janeiro participated in the study. Semi-structured interviews were used. Results: nursing affects healthcare waste management multidimensionally. Shortage of materials and work overload were identified as factors that influence professionals’ decision-making and increase the risk of improper waste disposal. The lack of knowledge on the subject also influences nursing practice. However, professionals value actions related to hazardous waste. Final Considerations: nursing professionals recognize themselves in healthcare waste management and understand the need to develop systemic awareness for sustainable practice. RESUMEN Objetivos: comprender cómo la gestión de residuos sanitarios es desarrollada por los profesionales de enfermería en el ambiente hospitalario. Métodos: investigación cualitativa, cuyos referentes teóricos y metodológicos fueron la Teoría de la Complejidad y la Teoría Fundamentada. Participaron del estudio 32 profesionales de enfermería de un hospital público de Río de Janeiro. Se utilizaron entrevistas semiestructuradas. Resultados: la enfermería incide de forma multidimensional en la gestión de residuos sanitarios. La escasez de materiales y la sobrecarga de trabajo fueron identificados como factores que influyen en la toma de decisiones de los profesionales y aumentan la eliminación inadecuada de los residuos. La fragilidad del conocimiento sobre el tema también influye en la práctica de enfermería. Sin embargo, los profesionales valoran las actuaciones relacionadas con los residuos peligrosos. Consideraciones Finales: los profesionales de enfermería se reconocen en la gestión de los residuos de los servicios de salud y comprenden la necesidad de formar conciencia sistémica para la práctica sustentable. RESUMO Objetivos: compreender como o gerenciamento de resíduos de serviços de saúde é desenvolvido por profissionais de enfermagem no ambiente hospitalar. Métodos: pesquisa qualitativa, cujos referencias teórico e metodológico foram a Teoria da Complexidade e a Teoria Fundamentada nos Dados. Participaram do estudo 32 profissionais de enfermagem de um hospital público do Rio de Janeiro. Foram empregadas entrevistas semiestruturadas. Resultados: a enfermagem afeta o gerenciamento de resíduos de serviços de saúde de forma multidimensional. Escassez de materiais e sobrecarga de trabalho foram apontados como fatores que influenciam a tomada de decisão dos profissionais e potencializam descarte inadequado de resíduos. A fragilidade de conhecimentos sobre a temática também influencia a prática da enfermagem. Entretanto, os profissionais valorizam ações relacionadas aos resíduos perigosos. Considerações Finais: os profissionais de enfermagem se reconhecem no gerenciamento de resíduos de serviços de saúde e compreendem a necessidade da formação de uma consciência sistêmica para uma prática sustentável.